1996
DOI: 10.1016/s0140-6736(96)90075-6
|View full text |Cite
|
Sign up to set email alerts
|

Age at menopause as a risk factor for cardiovascular mortality

Abstract: SummaryBackground Although an association of occurrence of menopause and subsequent oestrogen deficiency with increased cardiovascular disease has been postulated, studies on this association have not shown convincing results. We investigated whether age at menopause is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(101 citation statements)
references
References 29 publications
(21 reference statements)
6
94
1
Order By: Relevance
“…An association between hysterectomy and early menopause has been reported [10], and the mechanism is thought to be reduced ovarian blood supply after hysterectomy. Early natural menopause is associated with increased risk of cardiovascular diseases [11], and the pathogenic factor is considered to be a longer exposure to cardiovascular risk factors without the protective actions of estrogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An association between hysterectomy and early menopause has been reported [10], and the mechanism is thought to be reduced ovarian blood supply after hysterectomy. Early natural menopause is associated with increased risk of cardiovascular diseases [11], and the pathogenic factor is considered to be a longer exposure to cardiovascular risk factors without the protective actions of estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study examining age at menopause and risk of cardiovascular diseases showed that early natural menopause was an independent risk factor for cardiovascular mortality, whereas age at menopause had no significant effect on cardiovascular mortality in women who had undergone hysterectomy [10]. Based on cross-sectional data from the Women’s Health Initiative (WHI) Study, Hsia et al [11] studied 1,501 women at a mean age of 62 years who reported to ever have had hysterectomy with or without oophorectomy and compared them to controls without such surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors include hypertension, insulin resistance, dyslipidaemia and oestrogen deficiency. Premenopausal women are relatively protected from cardiovascular disease, and premature ovarian failure increases cardiovascular mortality [84], presumably due to oestrogen deficiency. The effect of HRT on cardiovascular outcomes in postmenopausal women remains controversial, particularly in the light of recently published evidence from the Women’s Health Initiative and HERS II [85, 86].…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%
“…A number of studies have demonstrated that arterial compliance declined rapidly in hypertensive women during the perimenopausal period in a manner proportional to the decrease in endogenous level of estrogen [7, 8]. Consistent with the above findings, epidemiological studies suggest that menopause is a risk factor for CVD in women [27,28,29]. This effect is believed to be caused in part by the loss of estrogen which has multiple protective effects on the vascular system [30].…”
Section: Discussionmentioning
confidence: 77%